2022
DOI: 10.1111/pan.14564
|View full text |Cite
|
Sign up to set email alerts
|

Consumer research priorities for pediatric anesthesia and perioperative medicine

Abstract: Background Consumer‐driven research is increasingly being prioritized. Aim Our aim was to partner with consumers to identify the top 10 research priorities for pediatric anesthesia and perioperative medicine. The ACORN (Anesthesia Consumer Research Network) was formed to collaborate with children and families across Australia. Methods A prospective online survey was developed to generate research ideas from consumers. The survey was developed in Qualtrics, a survey research platform. Consumers were invited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In recent times, there have been considerable efforts to find a better balance between sufficient fasting times to avoid aspiration, while simultaneously reducing the negative physiological outcomes and stress on our young patients. This is also in line with consumer priorities for perioperative medicine 13 . Indeed, a study of children undergoing emergency surgery found the most common negative recollection was fasting, together with pain 14 .…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In recent times, there have been considerable efforts to find a better balance between sufficient fasting times to avoid aspiration, while simultaneously reducing the negative physiological outcomes and stress on our young patients. This is also in line with consumer priorities for perioperative medicine 13 . Indeed, a study of children undergoing emergency surgery found the most common negative recollection was fasting, together with pain 14 .…”
Section: Introductionsupporting
confidence: 66%
“…This is also in line with consumer priorities for perioperative medicine. 13 Indeed, a study of children undergoing emergency surgery found the most common negative recollection was fasting, together with pain. 14 as "water, carbohydrate rich fluids, specifically developed for perioperative use, pulp free fruit juice, clear cordial, black tea and coffee … excludes fluids containing particulate matter, soluble fibre, milkbased drinks and jelly."…”
Section: Introductionmentioning
confidence: 99%
“…This has come about from the recognition that the question the clinical and research teams are asking, or the answers they are seeking, may not clearly align with the priorities of the consumer, in the case of infant hernia surgery the patient and their parents or immediate caregivers. Some groups have sought to identify the anesthesia research priorities of consumers and clinicians as a way of directing future research, with the Anesthesia Consumer Research Network (ACORN) showing that consumers have a top priority of safer anesthesia for children 59 …”
Section: Consumer Engagement—priorities Of Parentsmentioning
confidence: 99%
“…Some groups have sought to identify the anesthesia research priorities of consumers and clinicians as a way of directing future research, with the Anesthesia Consumer Research Network (ACORN) showing that consumers have a top priority of safer anesthesia for children. 59 There is little evidence in the literature on what parental perceptions are of the important priorities for anesthesia, and fewer still in infants undergoing hernia surgery. The only study relevant to infant inguinal hernia surgery was a survey of parents specifically exploring neurodevelopment, and found that 40% of parents had concerns about the impact of anesthesia on neurodevelopment, and more than 49% were moderately or very concerned about their child undergoing anesthesia.…”
Section: Consumer Eng Ag Ement-prioritie S Of Parentsmentioning
confidence: 99%
“…44 The final 4 studies brought together patients, caregivers, and clinicians to determine the top 10 most important research priorities in anesthesia and perioperative care in the United Kingdom, Canada, and Australia. 37,39,41,43 Each of these studies asked patients and clinicians what questions they would like to see answered in future anesthesia research. Sommerfield et al 43 in Australia specifically focused on research priorities within pediatric anesthesia.…”
Section: Collaboratementioning
confidence: 99%